2006
DOI: 10.1080/01612840600643040
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Depression Among Elderly Thai Immigrants

Abstract: Because little is known about elderly Thai immigrants' conceptualization of depression, a qualitative descriptive research study was conducted to explore their perception of depression. Semi-structured individual face-to-face interviews were performed with a purposeful sampling of ten men and ten women aged 60 years and older at participants' homes or Thai Buddhist temples. The results revealed that depression was defined as feeling disappointment and pressure in the mind and included symptoms of isolation, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…Not surprisingly, we found that some immigrants were more likely to consult ethnic group leaders and informal support systems than medical professionals for emotional and mental problems. Similar findings were reported in other studies of health care utilization by immigrants and refugees in other geographical areas (Brown, 2001;Chiu et al, 2005;Fenta et al, 2007;Lin & Cheung, 1999;Sheikh & Furnham, 2000;Soonthornchaiya & Dancy, 2006). As literature indicates (Chiu et al, 2005;George, Larson, Koenig, & McCullough, 2000;Lin & Cheung, 1999;Nash & Stewart, 2002), it is important for health care providers to recognize the powerful influence of religion and spirituality on health care decisions that some immigrant and refugee women make, especially for those who do not have strong support systems.…”
Section: Implications For Practicesupporting
confidence: 78%
“…Not surprisingly, we found that some immigrants were more likely to consult ethnic group leaders and informal support systems than medical professionals for emotional and mental problems. Similar findings were reported in other studies of health care utilization by immigrants and refugees in other geographical areas (Brown, 2001;Chiu et al, 2005;Fenta et al, 2007;Lin & Cheung, 1999;Sheikh & Furnham, 2000;Soonthornchaiya & Dancy, 2006). As literature indicates (Chiu et al, 2005;George, Larson, Koenig, & McCullough, 2000;Lin & Cheung, 1999;Nash & Stewart, 2002), it is important for health care providers to recognize the powerful influence of religion and spirituality on health care decisions that some immigrant and refugee women make, especially for those who do not have strong support systems.…”
Section: Implications For Practicesupporting
confidence: 78%
“…Thirteen qualitative studies were included in the review. Eight studies were conducted in the USA (Ugarriza, 2002;Pierce et al, 2003;Barg et al, 2006;Soonthornchaiya & Dancy, 2006;Switzer et al, 2006;Black et al, 2007;Wittink et al, 2009;Conner et al, 2010), one in the UK (Lawrence et al, 2006), three in Sweden (Hedelin & Strandmark, 2001a,b;Hedelin & Jonsson, 2003) and one in New Zealand (Allan & Dixon, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In one of the few studies of U.S. Buddhists, Soonthornchaiya and Dancy (2006) examined how 20 Thai immigrants coped with depression. Common Buddhist coping methods included going to the temple, talking to a monk, and practicing meditation.…”
Section: Qualitative Research On (Mostly) Eastern Buddhistsmentioning
confidence: 99%